Rancang bangun sistem FlowTrackr: Aplikasi manajemen test case dan bug report berbasis web - Desril Fatra Aditama; Imelda Imelda (AITI, 2026)
Software testing is an essential stage to ensure application quality before deployment. Manual testing practices by Quality Assurance (QA) teams often face challenges, such as scattered test results and bug reports across multiple media, making them difficult to trace and prone to miscommunication. This study designs FlowTrackr, a web-based integrated application for centralized test case management and bug reporting. The development followed the Waterfall methodology, covering requirements analysis, system design, implementation, and testing. Functional testing across 10 scenarios confirmed that all features operated according to specifications, while User Acceptance Testing (UAT) involving 5 QA testers demonstrated that the system was easy to use and more efficient than manual methods. Compared with tools such as Jira, TestRail, and Bugzilla, which tend to be more complex, FlowTrackr offers a lightweight, practical solution for small teams. Therefore, FlowTrackr can serve as an alternative to support manual QA processes, making them more structured and well-documented.